Membangun Efektivitas Pembelajaran Digital di Pendidikan Jasmani melalui Pendekatan UTAUT - Insan Nuhari; Mahlil Fajri; Fithri Angelia Permana (Indo Publishing, 2025)
This study aims to evaluate students’ acceptance of the blended learning system in the Physical Education Study Program at Universitas Serambi Mekkah using the UTAUT (Unified Theory of Acceptance and Use of Technology) model. A descriptive quantitative approach was applied with a sample of 72 active students who had experienced at least one semester of blended learning. The instrument used was a 5-point Likert scale questionnaire covering four UTAUT constructs: Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions. The findings indicate that all constructs scored high to very high, with the following averages: Performance Expectancy (4.32), Effort Expectancy (4.15), Social Influence (3.94), and Facilitating Conditions (4.27). These results suggest that students positively accept the blended learning system in terms of perceived benefits, ease of use, social support, and enabling conditions. Therefore, blended learning is considered an effective and relevant instructional method in higher education for sports and physical education in the digital era.